Volume 10: Ocean Renewable Energy 2019
DOI: 10.1115/omae2019-96034
|View full text |Cite
|
Sign up to set email alerts
|

On Motion and Hydroelastic Analysis of a Floating Offshore Wind Turbine

Abstract: This study is concerned with motion analysis and hydroelastic response of a floating offshore wind turbine to wave loads. The novel floating structure, made of prestressed concrete, is designed to support multiple wind turbines, and it rotates according to the environmental loads to face the incoming wind. The floating structure is attached to a mooring line that allows the rotation of the structure in response to the environmental loads. The floating structure is an equilateral triangular platform. The wind t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 9 publications
0
6
0
Order By: Relevance
“…The floater is triangular, supporting three wind turbines. A preliminary hydroelastic analysis of the wind-tracing floater is given in Lamei et al (2019) and concept design of the structure is discussed in Li et al (2019). Similarly, WindSea (Carbon Trust 2015) is a wind-tracing concept where the mooring lines are connected by a turret bearing to allow the platform to rotate and face the incoming wind, see Fig.…”
Section: Multi-unit Floater Conceptmentioning
confidence: 99%
See 1 more Smart Citation
“…The floater is triangular, supporting three wind turbines. A preliminary hydroelastic analysis of the wind-tracing floater is given in Lamei et al (2019) and concept design of the structure is discussed in Li et al (2019). Similarly, WindSea (Carbon Trust 2015) is a wind-tracing concept where the mooring lines are connected by a turret bearing to allow the platform to rotate and face the incoming wind, see Fig.…”
Section: Multi-unit Floater Conceptmentioning
confidence: 99%
“…6 (for water depth h = −200 m and wave height H = 1 m). For co-directional wind flow to the towers, the total aerodynamic loading on the three rotors (standard 5 MW NREL turbine) reaches up to 3 MN at rated wind speed of U W = 11.4 m/s, see Lamei et al (2019) and Li et al (2019) for more details about this structure and the calculation.…”
Section: Hydrodynamic Loadsmentioning
confidence: 99%
“…Furthermore, the wind-tracing FOWT was introduced by Wong (2015) with three wind turbines and a weathervaning mechanism by turret-bearing mooring system. Preliminary analysis on its wave-induced responses and its motions to the combined wind and wave loads were reported by Lamei et al (2019) and Li et al (2019).…”
Section: Introductionmentioning
confidence: 99%
“…The type of floating platform is selected based on the mooring system, the number of wind turbines, site requirements, construction, grid connection, and operating conditions of the sea [13]. Recently, the concept of multiple wind turbines on a floating platform has drawn attention because they are more stable and enable the use of higher towers and hence greater capture of wind energy [14][15][16][17][18][19][20][21][22][23]. The installation and mooring costs can be reduced by employing multiple wind turbines on a single platform as they can share common mooring lines [24].…”
Section: Introductionmentioning
confidence: 99%
“…Jang et al [20] showed that the heave plates with a minimal increase of mass can reduce the pitch and heave motions of a multi-unit offshore floating wind turbine. The concept of a triangular-shaped floating platform with three wind turbines at each corner was presented in [21,22] that considered only hydrodynamic loads to study the motion and elastic responses of the structure. This concept used a wind-tracing floating structure with a single-point mooring system that allows for the entire platform to rotate in response to the change of the wind direction.…”
Section: Introductionmentioning
confidence: 99%